2011
DOI: 10.1039/c0cp02653k
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies of 31P NMR spectral properties of phosphanes and related compounds in solution

Abstract: Selected theoretical methods, basis sets and solvation models have been tested in their ability to predict 31 P NMR chemical shifts of large phosphorous-containing molecular systems in solution. The most efficient strategy was found to involve NMR shift calculations at the GIAO-MPW1K/ 6-311++G(2d,2p)//MPW1K/6-31G(d) level in combination with a dual solvation model including the explicit consideration of single solvent molecules and a continuum (PCM) solvation model. For larger systems it has also been establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 89 publications
3
67
0
Order By: Relevance
“…49 According to calculations in frames of the polarizable continuum model (PCM) 80 for several model compounds (H 3 PO 4 (4, 0.02 D), P(OEt) 3 (36, 1.50 D), (CH 3 ) 3 PO (7, 4.32 D)), the magnetic shielding difference in vacuum and in benzene (e = 2.3) should be negligible (less than 0.7 ppm) for non-polar molecules (Table S8, ESI †). From this point of view it can be expected that more polar molecules can be more sensitive to these effects than the less polar ones.…”
Section: Phase State Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…49 According to calculations in frames of the polarizable continuum model (PCM) 80 for several model compounds (H 3 PO 4 (4, 0.02 D), P(OEt) 3 (36, 1.50 D), (CH 3 ) 3 PO (7, 4.32 D)), the magnetic shielding difference in vacuum and in benzene (e = 2.3) should be negligible (less than 0.7 ppm) for non-polar molecules (Table S8, ESI †). From this point of view it can be expected that more polar molecules can be more sensitive to these effects than the less polar ones.…”
Section: Phase State Problemmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] In several systematic studies it was shown 48-55 that a satisfactory agreement between calculations and experiments is observed when quite a ''heavy'' basis set or high level of theory ‡ was used although deviations and exceptions were also found. In fact, there are relatively few reports on 31 P NMR CS calculations using quantum chemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Also, they are very promising as photocatalysts in hybrid solar fuels. [20][21][22][23][24][25][26][27] The Gauge-Including Atomic Orbital (GIAO) 28,29 method is one of the most widely used. Moreover, combining the diverse range of electronic properties and the ability to act as well-defined ligands for polynuclear transition metal clusters, POMs give us the opportunity to discover and design new molecular magnetic devices.…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][57][58][59][60] At the same time the examples of application of these approaches on phosphorus are rather sparse. [54][55][56] We used a combination (PBE1PBE/6-311G(2d,2p)//PBE1PBE/ 6-31+G(d)) that proved to be reliable and effective for 31 P NMR CS calculations. First, the geometry optimization in the frames of the DFT (PBE1PBE/6-31+G(d)) method predicts that these three main isomers are close in energy (Table 1).…”
Section: Structure Determinationmentioning
confidence: 99%
“…[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] However applications of similar approaches to analyze phosphorus compounds by DFT calculations of 31 P NMR parameters are very rare. [54][55][56] The study here shows that the interplay of the NMR experiment and theory is a powerful method for determining the relative configurations of pentacoordinate chiral spirophosphoranes. For the illustration several pentacoordinate spirophosphoranes bearing two six-membered (Betti based derivatives) and five-membered (α-aminocarbonic acid derivatives) rings at the phosphorus atom were used.…”
Section: Introductionmentioning
confidence: 99%